2018
DOI: 10.1371/journal.pone.0196947
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, in vitro antitumor and pro-oxidant activities of Glandora rosmarinifolia (Boraginaceae) essential oil

Abstract: The biological properties of essential oils have been demonstrated in the treatment of several diseases and to enhance the bioavailability of other drugs. In natural habitats the essential oils compounds may play important roles in the protection of the plants as antibacterials, antivirals, antifungals, insecticides and also against herbivores by reducing their appetite for such plants or by repelling undesirable others. We analyzed by gas-chromatography mass spectrometry the chemical composition of the essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Statistical analysis was carried out according to Poma et al . [13] by analysis of variance (one-way ANOVA) followed by Tukey’s test. Statistica ver.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analysis was carried out according to Poma et al . [13] by analysis of variance (one-way ANOVA) followed by Tukey’s test. Statistica ver.…”
Section: Methodsmentioning
confidence: 99%
“…Results were expressed as mean ± standard error (SE) of at least three different experiments performed in duplicate. All the chemicals were supplied by Sigma Aldrich Srl, Milan, Italy [46].…”
Section: Anti-and Pro-oxidant Activitymentioning
confidence: 99%
“…The cytotoxic action is of great importance in the applications of EOs against certain human pathogens as well as for the preservation of food [11]. Recently, medical studies showed a possible anticancer activity of some EOs, attributable to an antimutagenic (i.e., Salvia officinalis L., Origanum onites L. and compactum, Lavandula angustifolia EOs [12][13][14][15]) and prooxidant activity (i.e., Origanum compactum, Artemisia herba-alba and Cinnamomum camphora, Glandora rosmarinifolia EOs [16,17]). This latter is a fundamental property to reduce local tumor volume and cell proliferation [10].…”
Section: Introductionmentioning
confidence: 99%